2014
DOI: 10.1007/s11357-014-9647-y
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen deficiency does not decrease the in vitro osteogenic potential of rat adipose-derived mesenchymal stem cells

Abstract: Osteoporosis due to estrogen deficiency is an increasing bone health issue worldwide: new strategies are being studied for regenerative medicine of bone pathologies in these patients. The most commonly used cells for tissue engineering therapy are the bone marrow mesenchymal stem cells (BMSCs), but they might be negatively affected by aging and estrogen deficiency. Besides the general advantages of adipose-derived mesenchymal stem cells (ADSCs) over BMSCs, ADSCs also seem to be less affected by aging than BMSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Bone marrow mesenchymal stromal cells (BMSCs) are already being used in both acute and chronic tendon injuries as a therapeutic alternative because of their differentiation ability, constant release of paracrine factors, low immunogenicity and their ability to recruit host stem cells as described in an our review article (under review) and several studies [13e16]. In one of our previous in vitro studies, we also found that adipose-derived mesenchymal stromal cell (ADSC) viability and osteogenic differentiation are much less influenced by estrogen deficiency than are BMSCs [17]. Given the many practical benefits of ADSCs compared with BMSCs, ADSCs were considered for the treatment of tendon lesions.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Bone marrow mesenchymal stromal cells (BMSCs) are already being used in both acute and chronic tendon injuries as a therapeutic alternative because of their differentiation ability, constant release of paracrine factors, low immunogenicity and their ability to recruit host stem cells as described in an our review article (under review) and several studies [13e16]. In one of our previous in vitro studies, we also found that adipose-derived mesenchymal stromal cell (ADSC) viability and osteogenic differentiation are much less influenced by estrogen deficiency than are BMSCs [17]. Given the many practical benefits of ADSCs compared with BMSCs, ADSCs were considered for the treatment of tendon lesions.…”
Section: Introductionmentioning
confidence: 80%
“…Given the many practical benefits of ADSCs compared with BMSCs, ADSCs were considered for the treatment of tendon lesions. Indeed, ADSCs are easier to harvest with less discomfort, can be isolated in a larger quantity and show a higher proliferation rate, paracrine signaling and angiogenic properties in comparison to BMSCs [17]. Unlike BMSCs, little is known about the potential application of ADSCs for tendon regeneration and on the molecular events involved.…”
Section: Introductionmentioning
confidence: 99%
“…First, the experiments were performed only in 4 months old, male mice, that did not allow us to evaluate the age and sex related influences. Although differences in body composition between male and females mice were demonstrated (Berryman et al 2010), no effect of estrogens on the in vitro differentiation potential of AT-MSC has been reported (Veronesi, et al 2014). On the other hand, we decided to perform the study in relative young animals to account for age-related alterations in MSC properties (Kim, et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on osteogenic potential of ASCs from OVX donors. Veronesi and colleagues found that ASC clonogenicity, gene expression ( SPP1 and BGLAP ), and subsequent protein production (ALP activity and osteocalcin) of important osteogenic markers are unaffected by estrogen deficiency; some of these markers were higher in ASCs from OVX rats, including matrix mineralization while the production of pro-inflammatory cytokines [interleukin 1 beta (IL-1β) and IL-6] is similar to that of healthy cells [39]. These results provide a foundation for the use of autologous ASCs for bone pathologies, such as in OP women.…”
Section: Discussionmentioning
confidence: 99%